A new initiating system based on [(SiMes)Ru(PPh3)(Ind)Cl2] combined with azo-bis-isobutyronitrile in the polymerization and copolymerization of styrene and methyl methacrylate. Issue 1 (1st January 2017) - Al-Majid, Abdullah M.; Shamsan, Waseem Sharaf; Al-Odayn, Abdel-Basit Mohammed; Nahra, Fady; Aouak, Taieb; Nolan, Steven P.
Abstract: The homopolymerization and copolymerization of styrene and methyl methacrylate, initiated for the first time by the combination of azo-bis-isobutyronitrile (AIBN) with [(SiMes)Ru(PPh3 )(Ind)Cl2 ] complex. The reactions were successfully carried out, on a large scale, in presence this complex at 80 °C. It was concluded from the data obtained that the association of AIBN with the ruthenium complex reduces considerably the transfer reactions and leads to the controlled radical polymerization and the well-defined polymers.